RANCANG BANGUN SISTEM INFORMASI PENJUALAN HANDMADE BEADS VYOLET BERBASIS WEBSITE SEBAGAI MEDIA PROMOSI DI ERA GEN Z - Wulandari, Putri; Akramunnisa, Akramunnisa; Kurniadi, Wisnu (TRANSFORMASI, 2025)
This study aims to design and build a sales information system that meets the needs of the Gen Z era. The research method used is Research and Development (RD), with a waterfall development model approach consisting of five stages, namely: needs analysis, system design, writing program code, system testing, and implementation. This application was developed using the PHP programming language, HTML, Laravel Framework, Visual Studio Code as a code editor, XAMPP as a local server, MySQL as a database management system and Unified Modeling Language (UML) is used to design and describe the system. System testing was carried out using the black box method, and validation testing was carried out by two validators. The validation results showed that the first validator gave a score of 4, while the second validator gave a score of 3.6, resulting in an average score of 3.8 which is included in the "Very Feasible" category. In general, the sales information system that has been built is considered feasible to use and can help the sales process effectively and efficiently.Keywords: Rancang Bangun, Media Promosi, Gen Z, Website, PHP, Laravel, Black Box.